S5 The prevalence of asthma among cleaners in the UK. (2nd December 2011) - Alfajjam, S H; Stenton, C; Pless-Molluli, T; Howel, D
Abstract : Background: A number of epidemiological studies have shown a significant association between asthma and working as cleaner but reporting schemes and workforce surveys have identified typical features of occupational asthma in only a small minority. This discrepancy is either due to under-reporting; misattribution of work-exacerbated asthma, or development of occupational asthma with atypical symptoms that make it difficult to diagnose clinically. Aim: To determine the prevalence of asthma in a cohort of hospital and university cleaners in the UK. Methods: A respiratory symptom questionnaire was distributed to cleaners via their supervisors in 3 local hospital trusts and 2 universities. Results: 570 of an estimated 1400 cleaners (41%) returned the questionnaire but it is uncertain how many received it and so the true response rate is uncertain. Respiratory symptoms were common. 48% (272/570) of the cleaners reported at least one: 34% reported wheezing, 35% reported cough, 10% reported breathlessness and 11 % reported chest tightness. Night-time or early morning symptoms suggestive of asthma were reported by 35 % of the cleaners. 12% reported symptoms only following exposure to chemicals used at work. 14% of the cleaners reported physician-diagnosed asthma. In 30% asthma developed after they started work as a cleaner with a mean interval of 8 years. An additional 3% had taken asthma medication in the last 12 months without a clinical diagnosis of asthma. Conclusion: This study has identified a high prevalence of asthma among cleaners in the UK and a substantial proportion that developed it after first exposure to cleaning agents. Symptoms on exposure to cleaning agents were also common. Further investigation of the risk factors for asthma and the work-relatedness of the symptoms of asthmatic cleaners are planned.